2021
DOI: 10.1021/acs.chemmater.1c02951
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Cation Exchange for Mercury Chalcogenide 2D Nanoplatelets and Its Application for Alloys

Abstract: II–VI two-dimensional (2D) nanoplatelets (NPLs) exhibit the narrowest optical features among nanocrystals (NCs). This property remains true for Hg-based NPLs, despite a cation exchange procedure to obtain them from Cd-based NPLs, which leads to structural defects (poorly defined edges and voids) inducing inhomogeneous broadening. Here, we propose an optimized procedure for which a solvent, surface chemistry, and reaction conditions are rationally considered. The procedure is applied to the growth of alloyed Hg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(60 citation statements)
references
References 52 publications
5
55
0
Order By: Relevance
“…The first is alloying, as described in Section 2.3.2 above. Dabard et al demonstrated, for alloyed HgSe 1−x Te x NPL, 62 a bowing effect (i.e., a nonlinear dependence of the bandgap with alloy content) similar to the one observed for CdSe 1−x Te x NPLs 56 (Figure 7d). The introduction of heterostructures (Section 2.7) is another method to achieve spectral tunability while simultaneously enhancing particle stability and PL efficiency.…”
Section: Cation Exchange Onsupporting
confidence: 56%
See 2 more Smart Citations
“…The first is alloying, as described in Section 2.3.2 above. Dabard et al demonstrated, for alloyed HgSe 1−x Te x NPL, 62 a bowing effect (i.e., a nonlinear dependence of the bandgap with alloy content) similar to the one observed for CdSe 1−x Te x NPLs 56 (Figure 7d). The introduction of heterostructures (Section 2.7) is another method to achieve spectral tunability while simultaneously enhancing particle stability and PL efficiency.…”
Section: Cation Exchange Onsupporting
confidence: 56%
“…This paradox has been resolved by Dabard et al, who demonstrated that selection rules and band mixing induce similar optically active transitions in the mercury chalcogenide NPLs. 62 The second-factor complicating feature in the optical absorption of colloidal NPLs, excitons, is a distinguishing characteristic of colloidal NPL structures. Excitons, representing a deviation from plane-wave delocalization of electrons and holes, are electron−hole pairs bound by Coulombic attraction at an energy lower than the bandgap of free carriers.…”
Section: Electronic Structure Of a Quantum Well Semiconductormentioning
confidence: 99%
See 1 more Smart Citation
“…43 Continuous variation in HgSexTe1-x nanoparticles doping from n to p type by varying the nanoparticle composition has been evidenced by energy band diagram determination and TR-PES measurement. 44 Development of CQDs based solar cells strongly depends on charge collection efficiency. Determining the CQDs/electrode electronic coupling is of high interest.…”
Section: Colloidal Quantum Dotsmentioning
confidence: 99%
“…To date, two - dimensional CdTe nanostructures have been reported in the form of zincblende structured NPLs, wurtzite structured nanoribbons and CdTe nanosheets. , In 2013, Pedetti et al optimized the synthesis protocol for the colloidal synthesis of CdTe NPLs with zincblende structure, yielding NPL populations of different thicknesses defined with atomic precision. Despite such advances, the emission PLQY of CdTe NPLs is still limited to ∼1% , and no study has so far investigated their emission properties under ionizing radiation excitation.…”
mentioning
confidence: 99%